Analysis of Behaviour Support System for Mass Rapid Transit Underground Station Using Numerical Modelling Method - Razuhanafi Mat Yazid, Muhamad; Fikri, Muhammad; Che Mamat, Rufaizal; Md. Rahim, Syazwan; Mohd Taib, Aizat (International Journal of Engineering and Technology, 2019)
Deep basement construction has always been extensively constructed in urban areas especially in Kuala Lumpur where the area is dense and limited. The design of basement retaining wall and its support system involves careful analysis, design and monitoring system. The focus in this study is to model the actual cases on site by using Finite Element Software Plaxis2D. The site is located in Kenny Hill Formation categorized as a completely decomposed rock and generally has the consistency of a clayey silt soil. This study indicates that the numerical analyses can be constructive tools to predict the behaviour of soil during installation of support systems and excavations. The results obtained from the analysis recorded maximum deflection value of the retaining wall at 32.4 mm which occurred on the left wall at the last stage of construction, whereas the bending moment, shear force and maximum axial force of the retaining wall recorded 5232 kN/m, 1860 kNm and 4155 kN/m respectively. The most critical condition can be seen at the last stage of simulation. At this stage, the safety factor was tested and the value obtained was 2.3 which exceeded the geotechnical global standards.Â Â